The Role of c-Jun and Autocrine Signaling Loops in the Control of Repair Schwann Cells and Regeneration - Jessen, Kristjan R.; Mirsky, Rhona (Frontiers in Cellular Neuroscience, 2022)
ABSTRACT After nerve injury, both Schwann cells neurons switch to pro-regenerative states. For Schwann cells, this involves reprograming of myelin and Remak cells to repair Schwann cells that provide the signals and mechanisms needed for the survival of injured neurons, myelin clearance, axonal regeneration and target reinnervation. Because functional repair cells are essential for regeneration, it is unfortunate that their phenotype is not robust. Repair cell activation falters during aging and the repair phenotype fades during chronic denervation. These malfunctions are important reasons for the poor outcomes after nerve damage in humans. This review will discuss injury-induced Schwann cell reprogramming and the concept of the repair Schwann cell, and consider the molecular control of these cells with emphasis on c-Jun. This transcription factor is required for the generation of functional repair cells, and failure of c-Jun expression is implicated in repair cell failures in aging animals and during chronic denervation. Elevating c-Jun expression in repair cells promotes regeneration, showing in principle that targeting repair cells is an effective way of improving nerve repair. In this context, we will outline the emerging evidence that repair cells are sustained by autocrine signalling loops, attractive targets for interventions aimed at promoting regeneration